Analisis Faktor Kepercayaan dalam Penggunaan E-Wallet Oleh Mahasiswa: Studi Keamanan dan Kemudahan (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The development of financial technology (fintech) has encouraged the increasing use of e-wallets as a digital payment method, especially among students. However, user trust in e-wallets is still influenced by security and ease of use factors. This study aims to analyze the influence of security and convenience on the level of student confidence in using e-wallets and determine the most dominant factors in building this trust. This study uses a quantitative method with a descriptive and inferential approach, where data is collected through a questionnaire of 100 students from three polytechnics in Palembang City. The analysis was carried out using descriptive statistics, multiple linear regression tests, and validity and reliability tests to measure the relationship between the variables of safety, ease, and trust. The results showed that security had a more dominant influence than ease in forming student trust in e-wallets, with a regression coefficient of 0.72 for security and 0.65 for convenience. The most influential security factors are two-factor authentication (2FA) and data encryption, while the most significant convenience factor is the intuitive application interface. The conclusion of this study is that e-wallet providers need to focus more on improving security features without neglecting the aspect of ease of use to increase user trust and loyalty, especially among students.